The reliability of sullivan emotional intelligence scale for children in Malaysian context using rasch measurement model - Norfishah Mat Rabi (Tanjong Malim, 2019)
The reliability of sullivan emotional intelligence scale for children in Malaysian context using rasch measurement model by Norfishah Mat Rabi